DESULFATION OF WET-PROCESS PHOSPHORIC ACID USING POTASSIUM CARBONATE (K₂CO₃) (Universal International Scientific Journal, 2026)
JSC “Ammophos-Maxam” is well known for the production of ammophos fertilizersbased on concentrated phosphorites. In the production process, extraction phosphoric acid (EPA)obtained by the dihydrate process is used as a raw material; its composition contains 18–19%phosphorus pentoxide (P2O5). The low P2O5 concentration in EPA significantly increases heat andenergy consumption per unit of final product during the stages of evaporation, purification, andgranulation in the production of high-phosphorus fertilizers. In the Republic, extensive efforts arecurrently being undertaken in this area. This article presents recent research results on the purificationof dihydrate-process phosphoric acid from impurities carried out at JSC “Ammophos-Maxam”
Keywords: phosphorus; extraction phosphoric acid (EPA); Central Kyzylkum